The aplication of electronic commerce in the distribution of insurance services - Piljan Ivan; Piljan Tatjana; Cogoljević Dušan (Trendovi u Poslovanju)
The paper describes the importance of information and communication technology for the development of the insurance companies, with special emphasis on the current development and potential for further development of marketing, and the distribution of insurance products in particular, which relies on information and communication technologies, especially the Internet. A special place here is reserved for the internet marketing as the most common of Internet uses among insurance companies. Transforming business processes so that they comply with the principles of electronic commerce will in the neaar future become common even in smaller businesses, formerly conservative financial institutions, e.g. insurance companies, are increasingly turning to e-insurance which, despite high costs of its introduction and initial problems in the operation, are to be relied upon in the near future. Therefore, in many countries, it is becoming accepted, to a greater or lesser extent. Mobile communication brings the biggest changes in electronic commerce. Even today, its prevalence among consumers offers great opportunities for service providers. Insurance companies in our country at this moment do not offer their services through this specific communication channel, but in the very near future changes can be expected in this field, due to the fact that the prerequisites for that exist in Serbia. This is supported by information that some insurance companies in the neighboring countries have already activated their first applications for smart phones and similar applications in the Serbian banking industry already exist.